Solid-oil separation of coal tar residue to reduce polycyclic aromatic hydrocarbons via microwave-assisted extraction - Feiyue, Gao; Chuncai, Zhou; Zihao, Wang; Weiwei, Zhu; Xin, Wang; Guijian, Liu (Journal of environmental management, 2023)
Coal tar residue (CTR) is acknowledged as hazardous industrial waste with high contents of carbon and toxic polycyclic aromatic hydrocarbons (PAHs). Microwave-assisted extraction for separating tar and residue in CTR was investigated to reduce the content of PAHs. The key operating factors such as solvent type, solvent addition amount, radiation temperature, and radiation time in the extraction process were evaluated. Results showed that extreme extraction performance in the solvent with cyclic structure was attained, and an enhancement in extraction efficiency was achieved in elevated solvent addition amount, radiation temperature, or radiation time in a certain range. The optimized conditions were determined as benzene was chosen as extractant, solvent-solid ratio of 5:1 mL/g, radiation temperature of 75 °C, and radiation time of 10 min. Relative extraction efficiency of CTR and reduction efficiency of 16 priority control PAHs were 28.70% and 92.82%, respectively. According to the characterizations of extracted residue (MCTR) and tar (MCT) under optimum experimental conditions, it is possible to convert them into value-added products (carbon materials, solid fuels, or chemicals). Solid-oil separation via microwave-assisted extraction is a safe and high-valued utilization approach for CTR. •Reducing the content of PAHs in coal tar residue by microwave-assisted extraction was studied.•Extraction yield of microwave-assisted extraction was up to 28.70%.•The highest reduction efficiency of 16 priority control PAHs was 92.82%.